मराठी

If f(x) = 3x + 5, g(x) = 6x − 1, then find (f+g)(x) - Mathematics and Statistics

Advertisements
Advertisements

प्रश्न

If f(x) = 3x + 5, `"g"(x)` = 6x − 1, then find `("f" + "g") (x)`

बेरीज

उत्तर

f(x) = 3x + 5, `"g"(x)` = 6x – 1
`("f" + "g")  x = "f"(x) + "g"(x)` 
= 3x + 5 + 6x – 1
= 9x + 4

shaalaa.com
Fundamental Functions
  या प्रश्नात किंवा उत्तरात काही त्रुटी आहे का?
पाठ 2: Functions - Exercise 2.1 [पृष्ठ ३१]

APPEARS IN

Share
Notifications

Englishहिंदीमराठी


      Forgot password?
Use app×